(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The situation with tuberculosis among children is a kind of indicator of the epidemiological situation among adults. In the Republic of Uzbekistan, thanks to the established practice of large-scale state prevention of tuberculosis, the epidemiological situation has improved, and there is a tendency to reduce the prevalence of tuberculosis among children and adolescents. Particular difficulties are presented by the differential diagnosis of infection with Mycobacterium tuberculosis (MBT) as a manifestation of latent tuberculosis infection and tuberculosis of the intrathoracic lymph nodes [8, 9]. These conditions are often accompanied by similar immunological reactivity and manifestations of intoxication syndrome, which is not specific and is caused by tuberculosis infection and concomitant diseases [3, 4, 8, 10]. Tuberculosis in children from large families has a more severe course, determined by the prevalence of the process, the frequency of complicated courses, and forms of tuberculosis, which is due to the later detection of the disease compared to children from small families.